Effects of supplementation with vitamins C and E on the acute inflammatory response in Piaractus mesopotamicus - Bozzo, Fabiana Rizzo [UNESP]; Claudiano, Gustavo Da Silva; Yunis-aguinaga, Jefferson; Marcusso, Paulo Fernandes [UNESP]; Engrácia, Jair Rodini [UNESP]; Moraes, Julieta Rodini Engrácia De [UNESP] (Universidade Federal de Goiás, 2023)
Vitamins C and E are potent antioxidants that reduces the harmful effects of stress in several species including fish. In this study, it was evaluated the effect of vitamins C, E and their combination in the acute aerocystitis induced by inactivated Aeromonas hydrophila in pacu. 288 fish were distributed into 4 groups supplemented for 90 days: G1-control; G2-supplemented with 500 mg of Vitamin C; G3-supplemented with 500 mg of Vitamin E; G4-supplemented with 500 mg of Vitamin C + 500 mg of Vitamin E. The fish were divided in three groups, the first was not inoculated; second were inoculated in the swim bladder with 3 x 109 CFU of inactivated A. hydrophila and the last one with saline. The inflammatory exudate was collected from the swim bladder for assessment of cellular component and cytochemistry. The results showed higher accumulation of leukocytes in fish inoculated with bacteria. Cytochemistry was effective identifying thrombocytes, lymphocytes, macrophages and, granulocytes present in the exudate. It was also observed fish that received supplementation with vitamins presented higher accumulation of total cells in the exudate with a predominance of lymphocytes and thrombocytes. These results suggested that supplementation with vitamins improved the immunological responses.
Keywords: Aeromonas hydrophila; cytochemistry; pacu; swim bladder